Remuneração executiva e desempenho : evidências empíricas no mercado de capitais brasileiro - Oliveira, Isaac Gezer Silva de (2014)
The objective of this dissertation is to analyze the relation between management compensation and firm performance of Brazilian public listed companies at BM&FBOVESPA. The theoretical supposes that the incentive contract corroborates with the interests alignment between shareholders and managers and acts as a mechanism of corporate governance in order to drive the managers efforts for maximization of firm value. The sample is 100 more liquid listed firms in share trading at BM&FBOVESPA during the period of 2010 to 2012, for 296 sample observations. Data was obtained from the Reference Forms of Brazilian SEC (Comissão de Valores Mobiliários — CVM) and from Economática® as well from Thomson Reuters®. Eight hypotheses were tested as well as OLS regression models with unbalanced panel data, using the total compensation as the dependent variable and, for independent variables, variables concerning performance, firm value, size, ownership structure, corporate governance and control variables as well. To verify the factors that explain the usage of stock options and bonus programs, logit models were used. The results show that, in the selected sample, the greater the company size, board and firm value, the greater will be the manager compensation. Some industries like mining, chemistry, oil and gas, also plays a positive influence on manager compensation. Further, there is inverse relationship between total manager compensation and ownership concentration, the public rights of control and the governance classification set by BM&FBOVESPA. A greater firm value influences the utilization of stock options, as well as the use of bonus, being this impacted by grater firm performance. There were also robust check tests estimated by random effects, clustered standard-errors, dynamic models but the results remained the same. Therefore that the executive compensation is related with the corporate value, creating wealth to the shareholders; but the lack of relation with operational performance suggests failures on the compensation system which still depends on greater transparency and other governance mechanisms to align the interests of CEOs and shareholders.